HemisFear: A Virtual Reality Exposure Therapy Prototype Driven by Cross-Cultural Understanding of Dog Phobia - Sauer, Jacob; Riecke, Bernhard E (ACM CHI, 2025)
Cynophobia, the fear of dogs, is a common and debilitating phobia. Live exposure therapy is first-line treatment for many phobias, but using live dogs may be expensive and unpredictable. Virtual reality exposure therapy (VRET) is a promising alternative, but remains underexplored for cynophobia. Furthermore, existing VRET designs seldom account for cultural backgrounds, which influence cynophobia’s fear factors and severity. For example, stray dog encounters in South Asia pose unique risks compared to domestic dogs in the Anglosphere. This paper introduces HemisFear, a VRET prototype featuring two culturally informed environments: an Anglo-Western residence with domestic dogs, and an Indian city with strays. The Western environment was shaped by a content analysis of prior VRET literature, while participatory design interviews with individuals from India (N = 4) informed the stray dog environment. By reconciling VRET principles with cultural sensitivities, HemisFear may offer a path towards effective and inclusive treatment for cynophobia.
Keywords: Riecke; Riecke_2025; bernhard-riecke; conferencePaper; jacob-sauer; proj--cynophobia; proj--hemisfear